WAKAMONO KOTOBA PADA MEDIA SOSIAL TWITTER - Kumala Sari, Febri Gita; Aibonotika, Arza; Rahayu, Nana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Twitter is one of the largest social media services in the world. The research are purposes to analyzing the formation of wakamono kotoba on social media Twitter with the aim of knowing the types of word formation used. This researchment used Tsujimura's theory of word formation, which is divided into 5 types. The data was analyzed for collecting the secondary, this is because to describe how to do formatting the words. In this research founded that the formation of a wakamono kotoba is not limited to only one type of word formation, but can go through two to three different types of word formation. In this research are found the most frequent tend of word formation in the clipping type.Key Words: Wakamono Kotoba, Social Media, Word Formation